The Influence of Leaf Age, Oxidizing Pre-Treatment and Serving Temperature on Sensory Characteristics of Ampelgading Robusta Coffee Leaves Tea - Kiki Fibrianto; Aswin Rizky Wardhana; Laila Yum Wahibah; Eka Shinta Wulandari (Faculty of Animal and Agricultural Sciences, Diponegoro University, 2019)
The cultivation of coffee plants produces leaf-waste which is only currently used for feed and fertilizer. Traditionally coffee leaves tea could be processed as “kopi kawa”, a popular tea-like beverage in West Sumatera, Indonesia. This research was aimed at characterizing the sensory profile of beverage made from Ampelgading Robusta coffee leaves by considering different leaves age, processing method, and serving temperature applying the Rate-All-That-Apply (RATA) method involving 111 consumer respondents. It was observed that the coffee leaves tea were sensorially dominated by green aroma and flavor, bitter taste, and astringent mouth-feel. The leaves age significantly affected 6 sensory attributes, i.e. sweet taste, sour taste, bitter taste, sweet flavor, earthy flavor, and woody flavor. Meanwhile the processing method (oxidized and non-oxidized pre-treatment) as well as serving temperature had no significant effect on the sensory perception of consumer although significant influences were recorded on the changing of total phenolic content, caffeine content, pH, and color parameters. As conclusion, sensory characteristic of Ampelgading robusta coffee leave tea was strongly affected by the age of leaf, regardless the pre-treatment process and serving temperature.